Expansion of Health Insurance in the Philippines : Evidence from Panel Data - Bredenkamp, Caryn; Capuno, Joseph; Kraft, Aleli; Poco, Louis; Quimbo, Stella; Tan, Carlos Antonio, Jr. (World Bank, Washington, DC, 2017)
In December 2012, the government of the Philippines passed the Sin Tax Law (RA 10351) which restructured and raised tobacco and alcohol taxes, while earmarking 85 percent of the incremental revenues for health. Of this 85 percent, 80 percent was intended to be used to provide free health insurance for poor and near-poor families through the National Health Insurance Program managed by PhilHealth, programs intended to speed progress of the health Millennium Development Goals, and programs to promote health awareness. The remaining 20 percent augments the financing of the Medical Assistance Program of the Department of Health (DOH), which is a hospital-based fund (in the name of mayors, congressmen, and DOH officials) that can be used at the discretion of the facility to cover the medical costs of those who cannot afford to pay, and also the DOH’s Health Facilities Enhancement Program which allows the DOH to supplement the local governments’ investments in health facilities. This reform was important from a health financing perspective.In November 2014, free health insurance coverage was also extended to the elderly. This paper assesses the extent to which the automatic enrollment of a large number of poor and elderly people into health insurance programs, as a result of the Sin Tax Law, has been associated with an increase in self-reported health insurance coverage, especially among the poorest quintiles and households living below the poverty line.